Bulk sediment mineralogy of gas hydrate reservoir at the East Nankai offshore production test site. (September 2015) - Egawa, Kosuke; Nishimura, Okio; Izumi, Shoko; Fukami, Eiji; Jin, Yusuke; Kida, Masato; Konno, Yoshihiro; Yoneda, Jun; Ito, Takuma; Suzuki, Kiyofumi; Nakatsuka, Yoshihiro; Nagao, Jiro
Abstract: Bulk sediment mineralogy was measured from a gas hydrate-bearing Middle Pleistocene deepwater turbidite interval at the offshore production test site of the Eastern Nankai Trough area. We used core samples recovered from a 60-m-long section of the borehole for semi-quantitative analysis of mineral and organic contents of the gas hydrate reservoir. Powder X-ray diffraction analysis, ignition loss test, and field-emission scanning electronic microscopy revealed the followings: (i) ten bulk minerals vary in concentration and most of them have a good exponential correlation with median grain size; (ii) the upper muddy section is dominated by coccolith-rich hemipelagites, whereas the middle and lower sections are characterized by relatively coccolith-poor, probably humic substance-rich turbiditic sediments; and (iii) the common occurrence of authigenic gypsum, siderite, and framboidal pyrite indicates early diagenesis in anoxic and relatively high salinity conditions probably associated with gas hydrate formation in some degree. Such mineralogical data can provide useful information on evaluation of thermal properties, geomechanical characteristics, effective permeability, and early diagenetic mechanism of the sediments to characterize and exploit gas hydrate reservoirs. Highlights: Bulk mineralogy is well correlated with median grain size variation. Calcareous nannofossils are dominant in the upper seal section. Humic substances are abundant in the lower and middle reservoir sections. Authigenesis of gypsum and siderite suggests diagenesis in high salinity condition.